Obeticholic acid and ferrostatin-1 differentially ameliorate non-alcoholic steatohepatitis in AMLN diet-fed ob/ob mice - Li, Shengjie; Zhuge, Aoxiang; Wang, Kaicen; Xia, Jiafeng; Wang, Qiangqiang; Han, Shengyi; Shen, Jian; Li, Lanjuan (Frontiers in Pharmacology, 2022)
Nonalcoholic fatty liver disease (NAFLD) and nonalcoholic steatohepatitis (NASH) are common chronic liver diseases with limited treatment options. Ob/ob mice (6 weeks old) were fed with the Control diet or amylin liver NASH (AMLN) diet for 24 weeks to establish the NASH, the AMLN diet-fed mice were treated with obeticholic acid (OCA), ferrostatin-1 (Fer-1) or their combination for 7 weeks. Finally, various clinical profiles were assessed. Our results indicate that Fer-1 exerts better effects on improving body weight, blood glucose levels, transaminase levels and insulin resistance than OCA. OCA has a profound effect on ameliorating lipid accumulation. OCA and Fer-1 differentially inhibit the activation of hepatic Kupffer cells and HSCs. The combination of OCA and Fer-1 significantly reduces inflammation and protects mice against liver oxidative stress. OCA and Fer-1 differentially reshape the intestinal microbiota and affect the hepatic lipidome. Our study compares the effects of OCA, Fer-1 and their combination on various clinical profiles in NASH. These data demonstrate that different drug combinations results in different improvements, and these discoveries provide a reference for the use of the OCA, Fer-1 and their combination in the clinical treatment of NAFLD/NASH.